National Security Implications of Virtual Currency - Baron, Joshua; O'Mahony, Angela; Manheim, David; Dion-Schwarz, Cynthia (RAND Corporation, 2023)
This report examines the feasibility for non-state actors, including terrorist and insurgent groups, to increase their political and/or economic power by deploying a virtual currency (VC) for use in regular economic transactions. This report should be of interest to policymakers interested in technology, counterterrorism, and intelligence and law enforcement issues, as well as for VC and cybersecurity researchers.